Shift of Pikukuh Karuhun Values due to Communication Technology Exposure to Baduy Society - Santa Lorita Simamora; Dicky Andika; Rizki Briandana; Widyastuti Widyastuti (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2021)
The purpose of this study was to determine the reality in the shift of meaning and loyalty of cultural values in the current generation and the millennial generation of the Baduy Dalam Cibeo, Kanekes, Banten. On the basis of the consideration that no matter how strong the culture binds individuals in a certain ethnicity, it is difficult to stem the consequences of interactions with other individuals outside of the ethnic group. Moreover, it cannot be denied that exposure to communication technology has touched the Inner Baduy tribe which is known for their loyalty to upholding their ancestral customs, i.e. neither allowed to touch nor use the results of technological engineering. The phenomenological studies’ methods used in this study were observation data collection techniques and interviews. The research subjects were 3-year-old children and 3 Baduy teenagers who had interacted with visitors from outside Baduy and had used digital media communication technology (Mobile Cellular). The results showed that social interaction with outside guests led to behavior that was contrary to Pikukuh, i.e. using a cell phone outside of Cibeo Village. This is a contradiction between the personal needs of adolescents in Baduy and the violation of cultural values.Keywords: Media exposure, communication technology, cultural values, cultural meaning Baduy ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui realitas pergeseran makna dan loyalitas nilai budaya pada generasi milenial Baduy Dalam Cibeo, Kanekes, Banten. Melalui dasar pertimbangan bahwa betapapun kuatnya budaya mengikat individu-individu dalam etnis tertentu, sulit untuk membendung konsekuensi interaksi dengan individu lain di luar kelompok etnis tersebut. Apalagi tidak dapat dipungkiri bahwa terpaan teknologi komunikasi telah menyentuh suku Baduy Dalam yang dikenal dengan loyalitasnya dalam memegang teguh adat nenek moyang, yaitu tidak boleh menyentuh atau menggunakan hasil rekayasa teknologi. Metode studi fenomenologi yang digunakan dalam penelitian ini adalah teknik pengumpulan data observasi dan wawancara. Subjek penelitian adalah anak usia 3 tahun dan 3 remaja Baduy yang pernah berinteraksi dengan pengunjung dari luar Baduy dan pernah menggunakan teknologi komunikasi media digital (Mobile Cellular). Hasil penelitian menunjukkan bahwa interaksi sosial dengan tamu luar menimbulkan perilaku yang bertentangan dengan Pikukuh, yaitu menggunakan telepon seluler di luar Desa Cibeo. Hal ini merupakan kontradiksi antara kebutuhan pribadi remaja Baduy dengan pelanggaran nilai-nilai budaya. Kata Kunci: Terpaan media, teknologi komunikasi, nilai budaya, makna budaya Baduy